Numerical and Experimental Study on Convective Heat Transfer Characteristics in Foam Materials - Hongyan Lu; Lixin Yang; Zhiyong Wu; Siqi Xu (Energies, 2020)
Foam materials are widely used in heat exchange because of their high porosity and large specific surface area. Correctly characterizing heat transfer characteristics is the key to ensuring efficient heat transfer. In this paper, single-blow transient test technology is used to experimentally measure the temperature. Silicon carbide ceramics with various thicknesses ranging from 30 to 105 mm and different pore structures were used in the experiments. The test was carried out at the velocity ranging from 0.5 to 1.8 m/s. The air temperature distributions of the inlet and outlet were obtained by processing the experimental data, and the regularity of the average volumetric heat transfer coefficient was obtained and analyzed. Subsequently, the simplified tetrakaidecahedron models with a porosity of 0.85 and 0.75 were used to analyze the heat transfer characteristics. The local thermal equilibrium and local thermal non-equilibrium at the pore scale were analyzed. By comparing the simulation with the experiment, it shows that the larger thickness affects local thermal equilibrium and leads to a decrease in the volumetric heat transfer coefficient. The conclusion can be used to guide the optimization of the design of foam material-mediated heat exchange equipment.